2014
DOI: 10.1111/sms.12277
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional cardiac adaptations to a 10‐week school‐based football intervention for 9–10‐year‐old children

Abstract: The present study investigated the cardiac effects of a 10-week football training intervention for school children aged 9-10 years using comprehensive transthoracic echocardiography as a part of a larger ongoing study. A total of 97 pupils from four school classes were clusterrandomized into a control group that maintained their usual activities (CON; two classes, n = 51, 21 boys and 30 girls) and a football training group that performed an additional 3 × 40 min of small-sided football training per week (FT; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 32 publications
10
74
0
4
Order By: Relevance
“…12 Since the 'FIFA 11 for Health' programme combines health education with physical activity, the average exercise intensity and activity level may not have been as high as in the previous small-sided football studies, and the improvements in Yo-Yo performance for young schoolchildren have been shown to be closely related to the time spent in the highest aerobic intensity zone. 13 Nonetheless, the modified 'FIFA 11 for Health' programme focusing on NCDs did include two weekly 45 min sessions rather than one 90 min session and did include at least 30 min/ week of small-sided games (2v2 to 5v5) with at least 20 min in the play football session and at least 10 min in the play fair session (see table 1). This study suggests that this protocol was sufficient to induce multiple effects on cardiorespiratory health and also to provide some improvements in sprint performance and intermittent exercise performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Since the 'FIFA 11 for Health' programme combines health education with physical activity, the average exercise intensity and activity level may not have been as high as in the previous small-sided football studies, and the improvements in Yo-Yo performance for young schoolchildren have been shown to be closely related to the time spent in the highest aerobic intensity zone. 13 Nonetheless, the modified 'FIFA 11 for Health' programme focusing on NCDs did include two weekly 45 min sessions rather than one 90 min session and did include at least 30 min/ week of small-sided games (2v2 to 5v5) with at least 20 min in the play football session and at least 10 min in the play fair session (see table 1). This study suggests that this protocol was sufficient to induce multiple effects on cardiorespiratory health and also to provide some improvements in sprint performance and intermittent exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] It has furthermore been shown that small-sided drills induce high heart rates (HRs), a high number of intense actions along with high involvement, technical success rates and training effects for boys and girls irrespective of body mass index (BMI), fitness level or prior experience with football. [12][13][14][15] It was therefore decided to implement each 90 min session of the 'FIFA 11 for Health' programme over two separate 45 min periods conducted at least 1 day apart, and to include a high number of small-sided games and drills in order to ensure exercise periods with high intensity and high involvement for all participants. The modifications to the health messages, which were based on a rigorous examination of the health challenges in Europe arising from NCDs and an examination of successful and unsuccessful health campaigns in the Western world, resulted in a programme providing health education focusing on physical activity, nutrition and abuse as well as positive thinking and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…() have also shown improved performance and endurance capacity as well as lower HR during submaximal exercise after 6 months of football training for 8–12‐year‐old overweight boys. It has also been shown that football training has considerable effects on cardiac structure and function (Hansen et al., ; Krustrup et al., ) and important positive effects on self‐esteem and attraction to physical activity (Faude et al., ; Seabra et al., ). Thus, the available studies on the health effects in children after football participation indicates that football training for children has several positive health‐related effects as observed for adults (Krustrup et al., , ; Randers et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, en este caso la reducción de la presión arterial fue no significativa estadísticamente aparte de la presión arterial diastólica en el grupo que realizó tres días de actividad física por semana (p=0.04). Krustrup et al (2014) llevaron a cabo un estudio con 97 niños de 9 a 10 años (divididos en grupos de práctica y control) que realizaron, adicionalmente a su actividad normal, tres sesiones a la semana de 40 minutos de fútbol. En dicho estudio no se mostraron cambios en la frecuencia cardiaca en reposo ni en la presión arterial.…”
Section: Discussionunclassified